Relationship of Knowledge and Attitude with Compliance from the Use of Personal Protective Equipment at Mitra Medika Amplas Hospital - Miranda, Melda; Yustina, Ida; Theo, Deli; Putri, Andin Rizqika Aliun (Budapest International Research and Critics University, 2021)
Infected health workers can also be a source of infection for patients and other health workers, due to the lack of personal protective equipment. This type of research is using a cross sectional design. The dependent variable of this study is compliance from the use of personal protective equipment, and the independent variables are knowledge and attitude. Knowledge is the result of human sensing to know about an object through its five senses. When using personal protective equipment, it is necessary to have compliance in the form of an attitude to be willing to obey and follow a specification, standard or rule that has been clearly regulated and issued by an authorized organization. The sample consisted of 100 health workers consisting of nurses and midwives, emergency room doctors, room doctors, specialist doctors and isolation room nurses. Data were collected through interviews using a questionnaire, then the data was analyzed using univariate table frequency distribution and bivariate analysis using the chi-square test. The conclusion of the research is that there is a significant relationship between knowledge and compliance from the use of personal protective equipment (p=0.020) and there is a significant relationship between attitude and compliance from the use of personal protective equipment (p=0.032).